Differences in PFAS exposure between Pacific pinnipeds: The Galapagos (Zalophus wollebaeki) and California (Zalophus californianus) sea lions - Ashley E. Cave; Isabella G. Livingston; Taylor M. Gregory; Eleanor C. Hawkins; Shelly Vaden; Marjorie Riofrío-Lazo; Diane Deresienski; Gregory A. Lewbart; Anthony J. Orr; Emily Griffith; Christopher Fuller; Mark J. Strynar; et al. (Marine Pollution Bulletin, 2026)

Metacommunity structural changes of Antarctic benthic invertebrates over the late Maastrichtian - Tasnuva Ming Khan; Rowan J. Whittle; James D. Witts; Huw J. Griffiths; Andrea Manica; Emily G. Mitchell (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Evaluating genetic and environmental controls on silicon accumulation in Populus trichocarpa leaves - Elizabeth Herndon; Emily G. Willman; Eleanor E. Wetter; Hui Li; Hunter B. Andrews; Ann Wymore; Madhavi Martin; Natalie A. Griffiths (Plant and Soil, 2025)

Skittish Males in High Latitudes: Complex Social and Acoustic Response of Adult Male Sperm Whales When Harassed by Orcas - Mel Cosentino; Emily T. Griffiths; Jade A. van Dam; Ceres H. van Dongen (Marine Mammal Science, 2025)

Quantifying placebo and trial participation effects on cognitive outcome measures in aging dogs - Katherine E. Simon; Katharine Russell; Alejandra Mondino; Chin-Chieh Yang; Beth C. Case; Zachary Anderson; Christine Whitley; Emily Griffith; Margaret E. Gruen; Natasha J. Olby (GeroScience, 2025)
The placebo effect, or the positive effects observed after an inert treatment which result from patients’ expectations for the therapy, is well documented in human medicine. However, in veterinary medicine, where owner’s expectations serve as a proxy for their pets, it remains underexplored, particularly for elderly dogs with cognitive decline. To address this gap, we examined 21 dogs (mean age: 12.85 years, SD: 1.46) from a placebo group in a randomized controlled trial (RCT) and compared their results to 17 dogs (mean age: 13.24 years, SD:1.56) from an observational, longitudinal study to distinguish placebo effect from trial participation effect. Both populations had statistically comparable baseline data. Cognitive changes were evaluated with two remotely administered owner questionnaires (Canine Cognitive Dysfunction Scale (CCDR) and Canine Dementia Scale (CADES)) and three in-house cognitive assessments (Cylinder Task, Detour and Sustained Gaze). We hypothesized that placebo effect would be greater than trial participation effect, particularly in owner-reported measures. Matched pairs T -tests and effect size calculations (Hedge’s g ) were used to calculate changes across 6 months. A strong ( g = 0.76), significant ( p = 0.021) improvement in CADES was observed in the placebo cohort after 6 months, while no changes were detected with CCDR. Conversely, the observational cohort showed a small ( g = 0.35) and significant ( p = 0.03) deterioration on CCDR, and no change in CADES. No significant changes were noted on the in-house cognitive assessments in either cohort. We conclude that study context influences remotely delivered owner assessments and CCDR is more robust against caregiver placebo effect in RCTs than CADES.

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

Network analyses on photographic surveys reveal that invertebrate predators do not structure epibenthos in the deep (~2000m) rocky Powell Basin, Weddell Sea, Antarctica - Tasnuva Ming Khan; Huw J. Griffiths; Rowan J. Whittle; Nile P. Stephenson; Katie M. Delahooke; Autun Purser; Andrea Manica; Emily G. Mitchell (Frontiers in Marine Science, 2024)
Predator-prey interactions in marine ecosystems control population sizes, maintain species richness, and provide intermediate disturbance. Such ecosystem structuring interactions may be rare in Antarctic epibenthic communities, which are unique among marine ecosystems worldwide for their dominance of soft bodied fauna (sponges, soft and hard corals, and echinoderms) and a simultaneous paucity of shell crushing predators (sharks, rays and durophagous decapods). In the shallow benthos, instead of durophagy, important Antarctic predators such as starfish, pycnogonids (sea spiders), nemertean worms, and nudibranchs employ grazing, scavenging, or sucking strategies. Far less is known about deep sea (>1000 m) Antarctic benthic communities due to the challenging nature of polar data collection, so that photographic surveys provide one of the only means of making in situ observations of these deep sea communities. We used seabed photographs of the deep (~2000m) slope of the Powell Basin, northwest Weddell Sea, taken by the Ocean Floor Observation and Bathymetry System on board the RV Polarstern (PS118, April 2019) to investigate the epibenthic community composition, and Bayesian Network Inference (BNI) to determine the ecological network, namely the ecological associations, including potential invertebrate predator-prey relationships between taxa. Photographs show that the rocky substrates of the basin slope support between 10-22 morphotaxa per photo, and highly abundant communities (density between 106 to 553 individuals/m 2 ). BNI results reveal a network of associations between the sessile and mobile suspension and filter feeding organisms and their physical environment. However, associations between invertebrate predators like starfish, and other organisms, were not detected in the network. This lack of inclusion within the network suggests that, despite the presence of these normally important mobile predators, invertebrate predator-prey interactions on the rocky Powell Basin slope do not have the same ecosystem-regulating impact that they do on shallow Antarctic epibenthic communities.

Rerouting of a major shipping lane through important harbour porpoise habitat caused no detectable change in annual occurrence or foraging patterns - Kylie Owen; Julia Carlström; Pia Eriksson; Mathias Andersson; Robin Nordström; Emilia Lalander; Signe Sveegaard; Line A. Kyhn; Emily T. Griffiths; Mel Cosentino; Jakob Tougaard (Marine Pollution Bulletin, 2024)

In-situ comparison of high-order detonations and low-order deflagration methodologies for underwater unexploded ordnance (UXO) disposal - Paul A. Lepper; Sei-Him Cheong; Stephen P. Robinson; Lian Wang; Jakob Tougaard; Emily T. Griffiths; John P. Hartley (Marine Pollution Bulletin, 2024)

Endangered shark species traded as “cação” in São Paulo during the COVID-19 lockdown: DNA-barcoding a snapshot of products - Veronica Zuccolo; Fernanda Moreira Rego; Emily Hughes; Andrew M. Griffiths (Molecular Biology Reports, 2023)
Background Elasmobranch populations are declining, predominantly driven by overfishing, and over a third of global sharks, rays, and chimeras are estimated to be threatened with extinction. In terms of trade, Brazil is ranked the eleventh-largest shark producer and the top importer of shark meat in the world. Research has shown that elasmobranchs are sold in Brazil under the name “cação” (a generic designation for cartilaginous fish) to overcome consumer resistance. Methodology and results This study used DNA barcoding to investigate the sale of sharks in the State of São Paulo during the COVID-19 lockdown. A total of 35 samples of “cação” were analysed, revealing six different shark species on sale, including Carcharhinus falciformis , Carcharhinus signatus , Carcharias taurus , Isurus oxyrinchus , and Isurus paucus, that are threatened with extinction according to the IUCN red list. This study demonstrates that vulnerable elasmobranchs are being commercialised under the label “cação” in the São Paulo State and Brazil. Conclusions Comparison of shark products traded before and during the COVID-19 pandemic showed no significant difference, suggesting lockdown did not affect patterns of species commercialisation. Effective fisheries and sale monitoring, correct product labelling legislation and increased consumer awareness that “cação” is shark are needed for appropriate conservation and management of shark populations in Brazil.

The power of eDNA sampling to investigate the impact of Australian mega-fires on platypus occupancy - Emily F. McColl-Gausden; Josh Griffiths; Luke Collins; Andrew R. Weeks; Reid Tingley (Biological Conservation, 2023)

Scientific challenges and biophysical knowledge gaps for implementing nutrient offset projects - Jing Lu; Joanne Burton; Alexandra Garzon-Garcia; Cameron Jackson; Michael Newham; Philip Bloesch; Ian Ramsay; Jenny Rogers; Merran Griffith; Emily Saeck; Michele A. Burford (Journal of Environmental Management, 2023)

Animal survival strategies in Neoproterozoic ice worlds - Huw J. Griffiths; Rowan J. Whittle; Emily G. Mitchell (Global Change Biology, 2023)
The timing of the first appearance of animals is of crucial importance for understanding the evolution of life on Earth. Although the fossil record places the earliest metazoans at 572–602 Ma, molecular clock studies suggest a far earlier origination, as far back as ~850 Ma. The difference in these dates would place the rise of animal life into a time period punctuated by multiple colossal, potentially global, glacial events. Although the two schools of thought debate the limitations of each other's methods, little time has been dedicated to how animal life might have survived if it did arise before or during these global glacial periods. The history of recent polar biota shows that organisms have found ways of persisting on and around the ice of the Antarctic continent throughout the Last Glacial Maximum (33–14 Ka), with some endemic species present before the breakup of Gondwana (180–23 Ma). Here we discuss the survival strategies and habitats of modern polar marine organisms in environments analogous to those that could have existed during Neoproterozoic glaciations. We discuss how, despite the apparent harshness of many ice covered, sub‐zero, Antarctic marine habitats, animal life thrives on, in and under the ice. Ice dominated systems and processes make some local environments more habitable through water circulation, oxygenation, terrigenous nutrient input and novel habitats. We consider how the physical conditions of Neoproterozoic glaciations would likely have dramatically impacted conditions for potential life in the shallows and erased any possible fossil evidence from the continental shelves. The recent glacial cycle has driven the evolution of Antarctica's unique fauna by acting as a “diversity pump,” and the same could be true for the late Proterozoic and the evolution of animal life on Earth, and the existence of life elsewhere in the universe on icy worlds or moons.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Acoustic‐based estimates of Cuvier's beaked whale ( Ziphius cavirostris ) density and abundance along the U.S. West Coast from drifting hydrophone recorders - Jay Barlow; Jeffrey E. Moore; Jennifer L. K. McCullough; Emily T. Griffiths (Marine Mammal Science, 2022)
An acoustic survey of Cuvier's beaked whales ( Ziphius cavirostris ) was conducted off the U.S. West Coast in August and September 2016 using drifting recorder systems with a vertical array of two hydrophones at a depth of ~110 m. Recorders were deployed 22 times to representatively cover a 1,058,000 km 2 study area from the shelf break to ~556 km offshore. Vertical angles to echolocation pulses were measured using the signal time‐difference‐of‐arrival on the two hydrophones. Echolocation pulses of Cuvier's beaked whales were identified from their arrival angles (always from below the array) and unique acoustic characteristics. The density and abundance of Cuvier's beaked whales were estimated using a group‐based point‐transect analysis with 2 min time snapshots. The area effectively surveyed was estimated using a maximum simulated likelihood approach to fit the observed distribution of signal arrival angles. The acoustic availability of whales during their dive cycle was estimated from the duration of acoustic encounters using a mark‐recapture approach. Overall, Cuvier's beaked whales were present during 0.60% of snapshots, and their estimated average density is 5.12 animals per 1,000 km 2 ( CV = 0.27). Their estimated abundance in the study area is 5,454 individuals (95% credibility intervals: 3,151 to 8,907).

Description of a new beaked whale echolocation pulse type in the California Current - Emily T. Griffiths; Jennifer L. Keating; Jay Barlow; Jeffrey E. Moore (Marine Mammal Science, 2019)

Liposomal Irinotecan Accumulates in Metastatic Lesions, Crosses the Blood-Tumor Barrier (BTB), and Prolongs Survival in an Experimental Model of Brain Metastases of Triple Negative Breast Cancer - Afroz S. Mohammad; Jessica I. Griffith; Chris E. Adkins; Neal Shah; Emily Sechrest; Emma L. Dolan; Tori B. Terrell-Hall; Bart S. Hendriks; Helen Lee; Paul R. Lockman (Pharmaceutical Research, 2018)

Drivers of promiscuous soybean associated rhizobia diversity in un-inoculated soil in Malawi - Mary Parr; Emily Griffith; Julie Grossman (Symbiosis, 2017)

Characterization of passive permeability at the blood–tumor barrier in five preclinical models of brain metastases of breast cancer - Chris E. Adkins; Afroz S. Mohammad; Tori B. Terrell-Hall; Emma L. Dolan; Neal Shah; Emily Sechrest; Jessica Griffith; Paul R. Lockman (Clinical & Experimental Metastasis, 2016)

Bottom‐up regulation of malaria population dynamics in mice co‐infected with lung‐migratory nematodes - Emily C. Griffiths; Karen Fairlie‐Clarke; Judith E. Allen; C. Jessica E. Metcalf; Andrea L. Graham (Ecology Letters, 2015)
When and how populations are regulated by bottom up vs. top down processes, and how those processes are affected by co‐occurring species, are poorly characterised across much of ecology. We are especially interested in the community ecology of parasites that must share a host. Here, we quantify how resources and immunity affect parasite propagation in experiments in near‐replicate ‘mesocosms’’ – i.e. mice infected with malaria ( Plasmodium chabaudi ) and nematodes ( Nippostrongylus brasiliensis ). Nematodes suppressed immune responses against malaria, and yet malaria populations were smaller in co‐infected hosts. Further analyses of within‐host epidemiology revealed that nematode co‐infection altered malaria propagation by suppressing target cell availability. This is the first demonstration that bottom‐up resource regulation may have earlier and stronger effects than top‐down immune mechanisms on within‐host community dynamics. Our findings demonstrate the potential power of experimental ecology to disentangle mechanisms of population regulation in complex communities.

Computational epigenetic profiling of CpG islets in MTHFR - Keat Wei; Heidi Sutherland; Emily Camilleri; Larisa M. Haupt; Lyn R. Griffiths; Siew Hua Gan (Molecular Biology Reports, 2014)

Partially functional Cenpa–GFP fusion protein causes increased chromosome missegregation and apoptosis during mouse embryogenesis - Paul Kalitsis; Kerry J. Fowler; Elizabeth Earle; Belinda Griffiths; Emily Howman; Ainsley J. Newson; K. H. Andy Choo (Chromosome Research, 2003)